The complete mitochondrial genome of Epeorus herklotsi (Ephemeroptera: Heptageniidae) from Longquan, Zhejiang, China and its phylogeny. Issue 2 (3rd July 2018) - Wu, Min-Jie; Yu, Li-Li
Abstract: The mitochondrial genome of Epeorus herklotsi (Ephemeroptera: Heptageniidae) from Longquan, Zhejiang province, China was a circular molecule of 15, 499 bp in length, containing 13 protein-coding genes, two ribosomal RNAs, 23 transfer RNAs, and a control region. The A + T content of the overall base composition of H-strand is 65.7%. All of the 13 protein-coding genes were begun with ATN as start codon except ND5 using GTG. ATP6, ATP8, COI, COIII, ND1, ND2, ND4L, and ND6 genes were terminated with TAA as stop codon, Cyt b ended with TAG and the other three protein-coding genes end with an incomplete stop codon (TA or T). In BI phylogenetic trees, the monophyly of the families Caenidae, Heptageniidae, Isonychiidae and Viemamellidae, and the genus Epeorus were strongly supported. Epeorus is a sister clade to Parafronurus, then cluster with Paegniodes .